Konfigurasi Dan Manajemen Koneksi Virtual Private Network (VPN) Antar Cabang Pada Kampus Teknologi Dan Bisnis Indonesia - Anisya Cendani; Erika Adelita Putri; Nanda Aprilia; Suci Liandra; Sumarlin; Romulo P Aritonang (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
Research aims to explain the use of virtual private networks (VPN) on the Indonesian Institute of Technology and Business Campus. The research method uses an exploratory method. Data analysis techniques using data collection, data reduction, data presentation and drawing conclusions. Meanwhile, the validity of the data is obtained through triangulation. The research results show the use of VPN on the Indonesian Institute of Technology and Business Campus for network security and data privacy. The Indonesian Institute of Technology and Business campus uses a Mikrotik router operating sistem server for the VPN network. To be able to use Mikrotik as a VPN server, configuration is required which includes IP pool configuration, IP router configuration, PPP configuration, DHCP server configuration, NAT by pass firewall configuration and IP security configuration. When choosing a VPN product, the campus considers the aspects of strong authentication, strong enough encryption, meeting standards, integration with other network services.